Prospects for Polar Tourism - Snyder, J.M (CABI, 2014)
Tourism or travel for pleasure results from a spreading of prosperity that is relatively recent in the history of mankind. Early travellers crossed oceans and continents to seek wealth, to colonize new lands, to exploit human populations and resources, or to right real or imagined wrongs. Travel for its own sake, to satisfy curiosity or to learn, required surplus wealth, time and motivation, and was rare before the 18th century. Among the earliest tourists were the scions of wealthy families, a tiny minority of the population, seeking culture in the discomforts and dangers of the European Grand Tour. During the 19th and early 20th centuries, steamships and expanding railroad networks vigorously promoted commercial tourism. Entrepreneurs exploited these new transport modes, allowing a broader spectrum of people affordable access to a wide variety of attractions. Following World War II, international prosperity, accompanied by commercial air travel and the omnipresent automobile, provided both the financial means and the transport modes for millions of people to travel. Commercial enterprises created resorts, theme parks, golf courses and other amusements, while simultaneously governments established more national parks and protected areas. Collectively, these diverse attractions now comprise a huge industry, reputedly the world’s largest, supplying tourist experiences on a grand scale, virtually unlimited by distance.